Hexagonal filters for ultrasound images (2014)
Most of the devices for acquisition and display of medical images use rectangular lattices even though there are other sampling strategies that can be more efficient in terms of resolution. This paper proposes an approach for ultrasound image enhancement that uses a hexagonal sampling scheme to display and process the images. The images were resampled on an interlaced grid. Interlaced sampling uses square pixels shifted half a pixel on alternate rows. Two types of hexagonal filters were designed and tested on ultrasound images: a statistical adaptive filter and an anisotropic diffusion filter. Results show improvements in signal-to-noise ratio and more natural representation of curved structures. © 2014 SPIE and IS&T.